Mathematical model of the gas flow in the shock front - Matveev, Sergey; Jaichibekov, Nurbulat (Eurasian Mathematical Journal, 2013)
In this paper, an approximate solution of the problem of the structure of shock waves in gases is presented. Changes of the average magnitude of density, speed and internal energy of gas along with the width of the shock wave are given. Dependence of the width of the jump on the Mach number is obtained and is compared with results of other authors.